Developing 'I Can Adapt' Science Module Using RIAS Learning for Enhanced Critical Thinking - Dwi Rahayu; Ahmad Muhlisin (Ta'dib, 2024)
In the context of Natural Science lessons, students often lack critical thinking skills. To address this challenge, the researchers developed the ÔÇ£I Can AdaptÔÇØ scientific module for students at SMP Negeri 10 Magelang. This study evaluates the moduleÔÇÖs viability, efficacy, and practicality using a research and development (R&D) approach based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The expert validation process confirmed the moduleÔÇÖs validity, with material experts rating it at 4.0 and teaching materials experts at 4.2. To assess efficacy, the researchers employed a one-group pretest-posttest design with paired sample t-test analysis. The results revealed a significant increase in critical thinking skills (p < 0.05), as indicated by a significance value of 0.00. The average N-Gain score of 0.83 falls within the high category. Furthermore, student questionnaires related to the RIAS-based science modules demonstrated a practicality level of 84.6%. Overall, the findings support the use of the ÔÇ£I Can AdaptÔÇØ RIAS-based science module as an effective tool for enhancing critical thinking abilities. ┬á